Associated factors of cleft lip and/or palate on patients in Vachira Phuket Hospital - Tanchotikul, Patama (Region 11 Medical Journal, 2023)
Objective : To describe the epidemiology and factors associated with cleft lip and/or palate on patients in Vachira Phuket Hospital. Methods : This descriptive study aimed to describe the epidemiology and factors associated with cleft lip and/or palate using data from questionnaire and medical record. The case of 132 patients with cleft lip and/or palate who come to treatment at Vachira Phuket Hospital from 2015 to 2022. Data was collected and analyzed including personal factors, gender, type of cleft lip and/or palate, parental factors, family history and factors during pregnancy. Results : Among 132 cases, 117 cases were Thai newborns and 15 involved foreign-born residents. The highest proportion were cleft lip and cleft palate (54.5%) followed by cleft palate (23.5%) and cleft lip (12.9%). Cleft lip and/or palate was slightly higher among females (53.8%). Patients with cleft lip and/or cleft palate were more frequently first-born (37.9%). There were 8 cases (6.1%) of syndromic cleft lip and/or palate. There was 20.5% of patients that have family history of cleft lip and/or cleft palate. The patients (1.5%) were their parents were consanguineously married. There is a statistically significant correlation between kinds of cleft lip and cleft palate and birth order (P=0.009) Conclusion : The highest proportion were cleft lip and cleft palate followed by cleft palate and cleft lip. All 3 types of cleft lip and/or palate were found in females more than males. Patients with cleft lip and/or cleft palate were more frequently first-born. A scientifically significant relationship was discovered between cleft lip and cleft palate and the kid born after the first.